Sizing of underwater gravity storage with solid weights participating in electricity markets. (4th August 2020) - Toubeau, Jean‐François; Ponsart, Chloé; Stevens, Christophe; De Grève, Zacharie; Vallée, François
Summary: This paper investigates the techno‐economic feasibility of the innovative concept of gravity energy storage, where heavy weights are raised and lowered in a water environment. Such eco‐friendly systems can be implemented in existing flooded pits or quarries, by leveraging the important depth of these cavities. Moreover, in addition to their long lifetime, they have no visual impact on the landscape, and offer a lot of flexibility to the power system. In this work, we firstly present an analytical study of the storage solution, which allows deriving tractable mathematical constraints describing its operation, such as its nonlinear speed‐power curves in both charge and discharge modes. These constraints are then integrated into the investment strategy of a merchant unit that seeks to maximize its profit by jointly participating in the energy and secondary reserve markets. The model is formulated within a stochastic framework to ensure robustness of sizing decisions in view of future market uncertainties. Results from a practical case study (on a natural cavity of 200 m) show that underwater gravity storage is a cost‐efficient technology that offers payback periods of less than 10 years, mainly due to its intrinsic low capital costs estimated at around 100 €/kWh. Abstract : The paper results from a multidisciplinary collaboration between university and industry (SinkFloatSolutions), and presents an innovative storage solution, that is, underground gravity storage. The principle relies on blocks that are raised and lowered in a natural water environment, such as flooded quarries, by exploiting the important depth of these cavities. The objective is to analyze the physical behavior of this system, and to evaluate its economic viability in the current competitive electricity markets.